KARIMUNJAWA DAN SISA BENDA BUDAYA MASYARAKAT PULAU-PULAU DI PERAIRAN UTARA JAWA - Lucas Partanda Koestoro (Berkala Arkeologi, 1997)
The remaining cultural objects in the Karimunjawa Islands are generally located in the vicinity of settlements, and most of them are in the form of graves which are mostly considered as sacred places so they are often visited on pilgrimages. For a long time in this area there have been contacts between local residents and other communities. The interactions that took place were not limited to shipping and trade, but some were caused by clashes between politics and power. as stated in several sources. Chinese sources, for example, mentioned that in 1293 Khubilai Khan's envoys, namely Shihpi and Kan Shing, afterwards from Belitung Island left for Java. In Karimunjawa they docked waiting for the opportunity to enter Tuban before traveling on the Kali Mas River via Sedayu.